Editorial - Lund, Jacob; Rasmussen, Mikkel Bolt (The Nordic Journal of Aesthetics, 2013)
Within the last 10–15 years we have witnessed a turn towards art and aesthetics amongst explicitly politically inclined philosophers and theorists whereas many art theorists and art critics have drawn the political aspects of contemporary art to the fore. With the present issue of The Nordic Journal of Aesthetics we want to address the relationship between aesthetics and politics and the ways in which this relationship has been and might be dealt with, analyzing the possible reasons for this current emphasis on the political potentials of art and aesthetics. Furthermore we aim to analyze the current interest in the different ways arts and aesthetics can have a political function and to contextualize this analysis within the broader return to aesthetics that have taken place within the humanities over the last 20 years.